Improvement of degraded soils by applying biochar, El Milagro district, Utcubamba, Amazonas - Vergara, Gino Alfredo (2025)
To improve the fertility of degraded soil, various techniques can be used. It's crucial to consider the pollutants present, the soil's characteristics, and treatment costs. Alternatives include the incorporation of organic matter, removal, stabilization, and the application of biochar. This research evaluated the impact of biochar on soil quality. Fifteen samples distributed in treatments with biochar at 5%, 10% and 15% concentrations for periods of 40, 35 and 30 days. The initial analysis was taken from a 200 m2 agricultural plot, which was divided into 20 plots of 10 m2. From these, 5 plots were selected and subdivided into 1m2 microplots at a depth of 30 cm. The analysis showed a low concentration of nutrients, mainly Carbon, Nitrogen and organic matter. Subsequently, biochar was prepared from organic waste and applied to soil samples. The results demonstrate that the most effective treatment was with 15% biochar, which improved soil quality. Finally, the research shows that applying biochar to degraded soil not only improves its quality but also contributes to environmental sustainability by repurposing organic waste.